Problem-Based Learning untuk Peningkatan Prestasi Belajar Mahasiswa: Penelitian Tindakan Kelas - Nikmah, Choirul; Putri, Rizky Dwi (Jurnal Pendidikan Akuntansi (JPAK), 2022)
Personal income tax (in income tax chapter 21) is a chapter of taxation that students have great difficulty with due to the many tax rates and mechanisms in calculations. In pretest, more than 50% of students were unable to finish the test on time and the average score was lower than the passing grade. This research aims to examine the use of problem-based learning to increase student activity as well as improve learning outcomes. This research was classroom action research that applied two cycles where each cycle consisted of planning, implementation, observation, and reflection. This research also used observation forms to measure lecturer and student activities and a closed questionnaire to examine student responses. The result showed that there was increased student and lecturer activity from cycle 1 to cycle 2. Furthermore, the average score also increased in cycle 2. Based on the questionnaire, applied PBL in a personal income tax course had the effect of making learning activities fun, increased the ease of understanding of the subject and introduced new experiences that connected the cases with daily life.